Isu antara perubahan iklim dan keadilan sosial: Sebuah kajian literatur: Issue between climate change and social equity: A literature Review - Cahyoko Edi Tando; Nurul Hikmah (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
This study analyzes the issue of climate change which is currently becoming a global issue and its relation to social equality. Climate change not only brings many disasters to biodiversity in nature but also has long-term impacts and some also have direct impacts on humans, both in the social, cultural, economic, health, educational and other fields. This research will focus on the field of public administration using a qualitative approach in the form of a literature review of several related articles. The focus of the discussion will also be on the causes of climate change and its impact on humans, then local wisdom as social eqality and Indonesia's national goals. The results of this study are to mention Indonesia as a contributor as one of the countries causing climate change, then its impact on humans in general, then local wisdom in Indonesia which should be a reinforcement in climate change mitigation and finally Indonesia's national goal which must be strengthened by local wisdom. Researchers review that there must be sustainability and a big commitment in terms of politics in Indonesia to continue to promote a green economy and renewable energy so as not to exacerbate climate change